The Influence of Corporate Governance on Corporate Social Responsibility Disclosure: Empirical Evidence from Indonesian Listed Companies 2021–2023 - Angir, Winna Octaviana; Feliana, Yie Ke (APSSAI, 2025)
Research aims: This study aims to determine the effect of corporate governance on corporate social responsibility in companies. Design/Methodology/Approach: This study uses secondary data, specifically annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. A total of 718 companies that meet the criteria were selected for analysis. Research findings: This study found that board independence, women on the board, and audit committee independence had no effect on corporate social responsibility disclosure. Meanwhile, board size and ownership concentration had a significant positive effect on corporate social responsibility disclosure. Theoretical contribution/Originality: This study fills the literature gap on the influence of board of commissioners' characteristics on CSR disclosure in Indonesia and examines the differences in findings from previous studies. Practitioner/Policy implication: This research provides guidance for companies in improving governance and supports regulators in strengthening CSR regulations.